France, Germany, Italy, and Spain : Explaining Differences in External Sector Performance Among Large Euro Area Countries. (IMF Staff Country Reports; Country Report, 2005)
This cross-country paper explains differences in external sector performance among four large euro area countries-France, Germany, Italy, and Spain. The paper discusses that during 2001-04, the performance of the external sector differed markedly among these four largest euro area countries. The study presented in this paper describes the evolution of the traditional determinants of exports and imports-domestic and foreign demand and cost and price competitiveness-and econometrically assesses their contributions to the evolution of trade volumes during the period mentioned.